Design and development of indigenous irrigation scheduler for drip irrigation system. (1st January 2012) - Kumar, Dilip; Singh, Harpreet; Hasan, M.; Dahake, V.R.; Rajan, Pradeep
Most of the irrigation controllers being used in India for drip irrigation system are imported and are very costly. There is a need to develop new indigenous irrigation controllers for the automation of drip irrigation system. The key objective of this paper is to report on an indigenous low cost time-based irrigation scheduler who performs user defined functions and output commands to derive appropriate actuators (i.e., solenoid valves, and motor). The developed prototype was tested at the Lab level and later at Centre for Protected Cultivation Technology (CPCT), Indian Agricultural Research Institute (IARI), New Delhi. So the development of a distributed in-field drip irrigation system is used, which offers the potential to increase yield and quality while saving water, but the irrigation control, data interface, and software design are the challenging issues.